Statistics Analysis the Effect of DiSTAD Learning Model on the Critical Thinking Skill and Learning Motivation - Ana Silfiani Rahmawati; Daniel Wolo (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
This study aims to determine the statistical analysis of the influence of the DiSTAD learning model on critical thinking skills, learning motivation, critical thinking skills and learning motivation. Data analysis using descriptive analysis and inferential analysis. The techniques used in data collection are test and non-test. The test technique is used to determine critical thinking skills and non-test techniques (quesioner) are used to determine the learning motivation of students. The results show that DiSTAD learning model gives a significantly positive effect to the critical thinking skills and it is shown by the output value of the t-test (5,529) (significance < 0.05). DiSTAD learning model gives a significantly positive effect to the student learning motivation, and it is shown by the output value of the t-test (5,531) (significance<0.05). The implementation of DiSTAD learning model gives a significantly more positive effect to the critical thinking skills and student learning motivation, and it is shown by the output value of the F-test (34,040) (significance < 0.05).